The Detrimental Effects of Sedentary Lifestyle on Human Health - Grzelak, Alicja (Journal of Education, Health and Sport, 2024)
Introduction: Sedentary lifestyles have become increasingly prevalent in modern societies, posing significant threats to human health. Technological advancements and the shift towards desk-based occupations have contributed to a substantial decline in physical activity, leading to a rise in various diseases. The detrimental effects of a sedentary lifestyle are far-reaching, impacting physical, mental, and cognitive aspects of well-being. Purpose of work: This review article aims to provide an examination of the ramifications of a sedentary lifestyle, exploring its multifaceted impact on the different domains of well-being. State of knowledge: Research examining the consequences of sedentary behavior has expanded significantly in recent years. Studies have consistently demonstrated the negative impact of sedentary lifestyles on various health outcomes, including increased risk of cardiovascular disease, metabolic disorders, musculoskeletal problems, and cognitive impairment [1][2]. Material and methods: The review is based on an in-depth analysis of current scientific literature, including recent publications in leading medical journals and relevant research studies. To identify relevant scientific publications and research studies, the review utilized comprehensive searches on well-known academic databases, including PubMed and Google Scholar. Summary: A sedentary lifestyle poses a significant threat to human health, contributing to a range of physical, mental, and cognitive ailments. Given the widespread prevalence of sedentary behaviors, particularly in modern societies, it is imperative to develop and implement effective strategies that encourage regular physical activity and reduce prolonged periods of inactivity. The review explores the key aspects of the detrimental effects of sedentary lifestyles, including their impact on cardiovascular health, metabolic processes, musculoskeletal well-being, and cognitive function.